From Climate to Security: Energy Transition and the New Geopolitics of Strategic Supply - Muhammad Ridho (Pen of Global Politics, 2026)
The global energy transition is reshaping international politics by shifting strategic attention from fossil fuel dependence toward critical minerals, industrial processing, and clean technology supply chains. As decarbonization accelerates, questions of climate policy are increasingly intertwined with security concerns, economic resilience, and geopolitical competition over strategic supply. This article examines how the energy transition transforms strategic supply into a central issue of contemporary geopolitics and global order. The study employs a qualitative research design grounded in document analysis and is guided by a geopolitical framework that links supply, dependency, and infrastructural power. Data are drawn from policy documents, institutional reports, regulatory texts, and scholarly materials related to critical minerals, clean energy manufacturing, industrial policy, and energy security. The analysis focuses on key dimensions including supply concentration, processing capacity, technological dependence, securitization, and differentiated state positioning within the emerging low-carbon economy. Strategic supply operates not only as an economic requirement of decarbonization but also as a mechanism through which states reorganize power, hierarchy, and vulnerability in the international system. The article argues that the energy transition is producing a security-centered politics of supply that redefines the geopolitical meaning of energy in the post-carbon era. Its contribution lies in integrating energy transition debates with a broader geopolitical understanding of strategic supply, order formation, and uneven global restructuring.